Women Politics in Türkiye and the Reflection for Indonesia’s Village Governance - Titis Thoriquttyas; Nita Rohmawati; Wisnu Yaqzan Naba (Bestuurskunde)
Although there has been significant progress in women’s rights in recent decades, traditional gender roles remain deeply embedded in Indonesia and Türkiye, particularly in rural areas. This study investigates a real-world instance of how women contribute to Turkish decision-making. The theoretical framework examines how gender dynamics, state policies, and leadership styles affect governance results in rural areas by incorporating two primary theories: participatory feminism and intersectionality. The first female Muhtar (elected village head of Türkiye), Gül Esin, made a name for herself as a role model for women across Türkiye, which had a lasting impact on village administration. This historical perspective highlights the increasing recognition of women’s perspectives within the village administration. This study uses library research to analyze Gül Esin’s leadership, village governance, and gender studies in Indonesia and Türkiye. This study uses document analysis to investigate the conceptualization and application of women’s leadership within Indonesian village governance. The findings underscore the critical role of women’s participation in village decision-making processes and demonstrate how their leadership contributes to more inclusive and effective governance. The study also offers policy recommendations, advocating for gender-sensitive policies and intersectional assessments in village governance, with a focus on marginalized communities. The results provide valuable insights into measures that can be implemented in similar situations regarding how village-level governance can be maximized to enhance women’s empowerment, particularly in the Indonesian context.